VLF/LF Reflectivity of the Polar Ionosphere 2 March-3 May 1975 - Rasmussen,John E.; McLain,Ralph J.; Turtle,John P. (1976)
The report provides a summary of high latitude ionospheric reflectivity as observed by the USAF high resolution VLF/LF ionosounder operating in northern Greenland. Ionospheric reflectivity parameters, including reflection heights and coefficients, are presented as a function of time of day. VLF long path propagation measurements, along with magnetometer and riometer data, are presented as supplemental information.